Empowering Teachers Through Training in Preparing Literacy-Based Electronic Teaching Materials as an Effort to Foster Paperless Culture - Wahyuni, Sri; Ihsan B, Ahmad Nurul; Febrianti, Nia; Ilham, Muh.; Suryani, Suryani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Community service activities with the theme of teacher empowerment through training on literacy-based electronic teaching materials as an effort to foster a paperless culture in the Apala Village, Bone Regency, were held on May 20, 2023, located at Barebbo 1 Public Middle School. The main problem with partner schools in learning is the use of digital literacy, while literacy learning activities in schools are urgently needed nowadays. To make this happen, human resources who are technologically literate are needed, while there are still some teachers who experience difficulties in preparing digital-based teaching materials. This community service activity aims to provide solutions to overcome problems experienced by partner schools through training and mentoring for teachers using the FlipBuilder software so that teachers are able to create innovative and fun learning. The results of the evaluation conducted for teachers found that 76% of the responses agreed with this training and could assist teachers in preparing interesting learning tools so as to create a fun learning atmosphere as well.